EP900 The impact of age on the management of patients with ovarian cancer. (1st November 2019) - Laudani, ME; Potenza, E; Fuso, L; Moro, F; Macchi, C; Ribotta, M; Zola, P
Abstract : Introduction/Background: Incidence of ovarian cancer increases with age and reaches a peak at 70 years. The aim of this study is to analyse the surgical and pharmacological therapies for patients affected by ovarian cancer identifying the best approach based not on the age but on the performance status. Methodology: We have conducted a single-center retrospective study. Patients with epithelial and non-epithelial ovarian tumours were included and ranked according to age at diagnosis in group A (≥70 years) and group B (<70 years). For each patient are considered: co-morbidities, performance status, FIGO stage, grading, histotype and treatment. Surgical treatment was differentiated into primary debulking surgery or interval debulking surgery, reporting extension, residual tumour, complications and days of hospitalization. Chemotherapy was administered for 3 or more cycles and the clinical response was evaluated at the end. Results: 134 patients were included in the study, 44 (32.8%) in group A and 90 (67.2%) in group B further divided into early and advanced stages. Optimal cytoreduction was achieved in 61.9% of the younger patients and in 36.1% of the older patients (p=0.01), although the surgical extension is not statistically significant different in the two groups. There is good correlation between overall survival and the performance status (p=0.0001), the age at diagnosis (p=0.004), the tumour stage (p=0.03) and the residual tumour (p=0.00001). The residual tumour (OR=2.399; p=0.006) and the performance status (OR=2.50; p=0.0001) resulted as an independent survival prognostic factors according to the multivariate Cox analysis. Conclusion: Our data suggest that patients aged ≥70 can tolerate radical surgical treatments in the same way as younger patients without a significant increase in morbidity, so an optimal cytoreduction should be considered the gold standard regardless of age. Therefore, our data underlines the importance of managing these patients within Gynecologic Oncology units equipped with a multidisciplinary team. Disclosure: Prof. Paolo Zola has received grants from AstraZeneca, Roche, Tesaro and PharmaMar.